Ocular Biometry of Primary Angle-Closure Disease in Younger Patients - Lin, Shufen; Zuo, Chengguo; Liu, Yuan; Xiao, Hui; Fang, Lei; Su, Yihua; Chen, Liming; Lin, Mingkai; Ling, Yunlan; Liu, Xing (Frontiers in Medicine, 2021)
Background: The purpose of this study was to analyze the ocular biometric parameters of primary angle-closure disease (PACD) in younger patients and compare them with those of elderly patients. Methods: This clinic-based, cross-sectional study included 154 eyes of 154 patients with PACD, consisting of 77 eyes of patients aged 40 years or younger and 77 eyes of patients older than 40. The PACD case definition was compatible with the ISGEO definition. Anterior segment parameters were measured by ultrasound biomicroscopy, axial length (AL) and lens thickness (LT) were measured by A-scan ultrasonography measurements, and the thickness of the retina and choroid were measured by optical coherence tomography. The differences in ocular biometric parameters between different age groups were compared by independent sample t-tests or Mann-Whitney U tests, and the correlation between the parameters and age was analyzed. Results: Compared to older PACD patients, the lens vault(LV),LV/LT and subfoveal choroidal thickness(SFCT) of younger patients were larger, while the peripheral and mean iris thickness(IT), trabecular-ciliary angle (TCA), ciliary body thickness (CBT), AL and LT were smaller (all P<0.01).There was no significant difference in anterior chamber depth, anterior chamber width, pupil diameter, angle opening distance at 500 μm from the scleral spur, anterior chamber angle and iris convexity between the two groups (all P>0.05). AL, LT, IT, TCA and CBT were positively associated with age (all P<0.001), while LV and SFCT were negatively associated with age (P=0.027 and P<0.001, respectively). Conclusions: Compared with elderly patients, younger PACD patients had more anteriorly positioned lenses, thinner and more anteriorly rotated ciliary bodies, thicker choroids, and shorter axial length. These characteristics might be important anatomical bases for the earlier onset of PACD and the higher risk of malignant glaucoma after filtering surgery.